Establishment and application of quadruple fluorescence quantitative RT-PCR method for the identification of waterfowl astrovirus - Li, Yang; Luo, Juan; Zhang, Fuyou; Shang, Jiajing; Deng, Chunran; Feng, Yingjie; Meng, Ge; Jiang, Wenming; Yu, Xiaohui; Liu, Guanhui; Liu, Hualei (Frontiers in Microbiology, 2024)
Avian astrovirus can infect a variety of poultry species and cause viral diarrhea, with a wide epidemic range strong pathogenicity and a high incidence. Among them, Duck astrovirus 3(DAstV-3), Duck astrovirus 4(DAstV-4), Goose astrovirus 1(GoAstV-1) and Goose astrovirus 2(GoAstV-2) are four types of astroviruses newly discovered in waterfowl in recent years. In order to realize the rapid detection of these four kinds of waterfowl stellate viruses, specific primers and probes were engineered to target a highly conserved region of ORF1b gene of DAstV-3, GoAstV-1 and GoAstV-2 and the ORF2 gene of DAstV-4, and a quadruple fluorescence quantitative RT-PCR method was developed. The results indicate that the method established in this study has good specificity and no cross reactivity with other pathogens. This method can detect viruses with a minimum concentration of 1 × 101 copies/μL for DAstV-4, GoAstV-1 and GoAstV-2, respectively, while the minimum concentration for DAstV-3 is 1 × 102 copies/μL. Compared with the routinely used RT-PCR method, the limit of detection by the multiplex RT-PCR lower. Both intra- and inter-assay variability tests revealed excellent reproducibility. This method was then used to analyze 269 field samples, and the results were verified by genome sequencing. In conclusion, this study presents a sensitive, accurate, and specific method for detecting DAstV-3, DAstV-4, GoAstV-1, and GoAstV-2 in a single reaction, enabling the monitoring and differential diagnosis of these four types of waterfowl astroviruses.